Study of the immunomodulatory properties of gamithromycin and dexamethasone in a lipopolysaccharide inflammation model in calves. (December 2015) - Plessers, E.; Watteyn, A.; Wyns, H.; Pardon, B.; De Backer, P.; Croubels, S.
Abstract: The aim of this study was to define the in vivo immunomodulatory properties of the macrolide antibiotic gamithromycin in calves, with respect to the acute phase response. Additionally, the corticosteroid dexamethasone was included as a positive control immunomodulatory drug. Both drugs, as well as their combination, were studied in a previously developed inflammation model, which was initiated by an intravenous lipopolysaccharide (LPS) challenge (0.5 μg/kg body weight). Twenty-four 4-week-old male Holstein Friesian calves were randomized into four groups: no pharmacological treatment (n = 6) or a pharmacological treatment with gamithromycin (n = 6), dexamethasone (n = 6) or their combination (n = 6) 1 h prior to LPS administration. Blood collection and clinical scoring were performed at regular time points until 72 h post LPS challenge. Plasma concentrations of selected cytokines (tumour necrosis factor-α (TNF-α) and interleukin 6 (IL-6)) and acute phase proteins (serum amyloid A and haptoglobin) were subsequently determined. Gamithromycin did not have any beneficial effect on the LPS-induced clinical signs (dyspnea, fever, anorexia and depression), nor on the studied inflammatory mediators. In the dexamethasone and combination groups, the occurrence of dyspnea and fever was not prominently influenced, although the calves recovered significantly faster from the challenge. Moreover, dexamethasone significantly inhibited the levels of TNF-α and IL-6, suggesting a key role for these cytokines in sickness behaviour. In conclusion, unlike dexamethasone, gamithromycin did not directly reduce cytokine release in an LPS inflammation model in calves. Highlights: We studied the immunomodulatory properties of gamithromycin, dexamethasone and their combination. We used a lipopolysaccharide-inflammation model in 4-week-old calves. We examined clinical signs, pro-inflammatory cytokines and acute phase proteins. Gamithromycin had no influence in this model. The administration of dexamethasone resulted in an attenuated response.